Fantasi Ideologis ar-Rajul dalam Cerpen Arinillah: Analisis Subjektivitas Slavoj Žižek - Sudarmawan, Habib; Mukhlis, Fahrudin; Fery Fauzi, Moh.; Mutamakkin, Nur; Maitsa, Khadija; Habib (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2025)
This study examines the ideological fantasy in representing the divine within literary discourse, as reflected in Taufik al-Hakim’s short story “Arinillah.” The research aims to analyze the ideological fantasy that structures the subjectivity of ar-Rajul using Slavoj Žižek’s concept of the subject within the symbolic order. Employing a qualitative descriptive method, the study operationally analyzes textual data in the form of words, phrases, sentences, and dialogues by identifying expressions of lack, desire, and symbolic substitution in the narrative. The analysis is conducted through close reading and theoretical interpretation based on Žižek’s framework of lack, fantasy, and the Real. The findings reveal that ar-Rajul’s subjectivity is constituted by ideological fantasy triggered by his son’s demand to “show Allah,” positioning him in a persistent state of lack. This fantasy manifests in symbolic strategies that attempt to represent the divine while simultaneously concealing the impossibility of a direct encounter with the Real.